Glucose Levels and Outcome After Primary Intraventricular Hemorrhage - Guo, Rui; Chen, Ruiqi; You, Chao; Ma, Lu; Li, Hao; Fang, Yuan (Current Neurovascular Research, 2019)
Background and Purpose: Hyperglycemia is reported to be associated with poor outcome in patients with spontaneous Intracerebral Hemorrhage (ICH), but the association between blood glucose level and outcomes in Primary Intraventricular Hemorrhage (PIVH) remains unclear. We sought to identify the parameters associated with admission hyperglycemia and analyze the impact of hyperglycemia on clinical outcome in patients with PIVH. Methods: Patients admitted to Department of Neurosurgery, West China Hospital with PIVH between 2010 and 2016 were retrospectively included in our study. Clinical, radiographic, and laboratory data were collected. Univariate and multivariate logistic regression analyses were used to identify independent predictors of poor outcomes. Results: One hundred and seventy patients were included in the analysis. Mean admission blood glucose level was 7.78±2.73 mmol/L and 10 patients (5.9%) had a history of diabetes mellitus. History of diabetes mellitus (P = 0.01; Odds Ratio [OR], 9.10; 95% Confidence Interval [CI], 1.64 to 50.54) was independent predictor of admission critical hyperglycemia defined at 8.17 mmol/L. Patients with admission critical hyperglycemia poorer outcome at discharge (P < 0.001) and 90 days (P < 0.001). After adjustment, admission blood glucose was significantly associated with discharge (P = 0.01; OR, 1.30; 95% CI, 1.06 to 1.59) and 90-day poor outcomes (P = 0.03; OR, 1.27; 95% CI, 1.03 to 1.58), as well as mortality at 90 days (P = 0.005; OR, 1.41; 95% CI, 1.11 to 1.78). In addition, admission critical hyperglycemia showed significantly increased the incidence rate of pneumonia in PIVH (P = 0.02; OR, 6.04; 95% CI 1.27 to 28.80) even after adjusting for the confounders. Conclusion: Admission blood glucose after PIVH is associated with discharge and 90-day poor outcomes, as well as mortality at 90 days. Admission hyperglycemia significantly increases the incidence rate of pneumonia in PIVH.
Keywords: hyperglycemia